AMPHETAMINE-INDUCED PSYCHOSIS LEADING TO HOMICIDE, SUICIDAL ATTEMPTS, AND DISORIENTATION: A CASE REPORT - Hussain Azad, Abrar; Shahzad Ali Khan,; Iram Bibi,; Ijaz Ali,; Pashma Wazir,; Shaaray Abrar Umar, (Journal of Ayub Medical College Abbottabad, 2024)
Amphetamine abuse leads to severe psychiatric and cardiovascular complications–psychosis, hallucinations and aggressive behavior. A 34-year-old male of five years noted history of amphetamine abuse and presented with amphetamine psychosis characterized by hallucinations, violent ideations and a recent suicide attempt is described in this case report. Previously under the influence of amphetamines, two years prior, the patient committed homicide. Patient had periods of very severe disorientation and agitation, history of suicidal ideation and violent thoughts toward others. Toxicology screenings were done, all were consistent with amphetamine presence. Diagnostic studies included cardiac biomarker elevations and abnormal electrolyte levels. Management was immediate and involved sedation, antipsychotic therapy and cardiovascular support, followed by long term psychiatric care and substance abuse rehabilitation. Here, chronic amphetamine abuse is shown to have profound psychiatric and behavioral effects and to require integrated treatment strategies to meet the complex needs of such patients.